Status of radiotherapy staff during the coronavirus disease 2019 (COVID‐19) epidemic in China. Issue Volume 5:Issues 4(2021) (8th November 2021) - Wang, Hui; Chen, Lulu; Liu, Zheming; Li, Ping; Xu, Tangpeng; Fu, Zhenmin; Song, Qibin; Wu, Hongxue; Li, Xiangpan
Abstract: Objective: In December 2019, coronavirus disease 2019 (COVID‐19) caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) broke out in Wuhan, China. The pandemic has posed a great challenge to radiation oncology departments, as interruptions in radiation therapy (RT) increase the risks of cancer recurrence or failure of the therapy as a whole. This study aimed to elucidate the impact of COVID‐19 on radiation therapy staff in China. Methods: As many working staff at different radiation oncology departments in China as possible were retrospectively enrolled from 23 January to 9 March 2020. They were then invited to answer a questionnaire, for essential data collection, from which their basic information, anxiety level, and workload were analyzed. Results: Seven (0.39%) of the 1 755 radiation therapy staff who answered the questionnaire had contracted COVID‐19, all of whom were from Wuhan. The factors influencing susceptibility were not sex ( P = 1.000), age ( P = 0.480), or comorbidities ( P = 0.600), but geographic location ( P < 0.001) and whether the respondent worked in a designated COVID‐19 hospital ( P = 0.003). In terms of protection procedures, four participants carried out basic, one second‐level and two third‐level protection procedures. The difference was not statistically significant ( P = 0.720). The infected respondents' anxiety level related to the outbreak (average score 6.57) was higher than that of their counterparts in Wuhan (5.18), as well as across the country (4.79), and 71.43% of those infected expressed the need for psychological interventions. During the epidemic, departments of 428 respondents (24.39%) shut down, while 76.71% of the respondents reported workload reduction. Conclusion: The factors related to COVID‐19 infection were the geographic location and whether the respondent worked in a designated COVID‐19 hospital. The infected respondents experienced greater psychological pressure than their uninfected counterparts and, therefore, required more psychological interventions.